Stereotactic Radiotherapy Plus Nivolumab in Patients with Locally Advanced Pancreatic Cancer: Results from Phase 1/2 Clinical CA209-9KH Trial - Milan Vošmik; Stanislav John; Josef Dvořák; Beatrice Mohelníková-Duchoňová; Bohuslav Melichar; Radka Lohynská; Aleš Ryška; Aml Mustafa Banni; Johana Krempová; Igor Sirák (Oncology and Therapy)
Abstract Introduction The dismal prognosis of pancreatic ductal adenocarcinoma (PDAC) highlights the urgent need for novel therapeutic strategies. Immune checkpoint inhibitors (ICIs) seem to be ineffective in most PDAC studies. Therefore, we conducted an open-label, multicenter phase 1/2 study (CA209-9KH) to evaluate the safety of stereotactic radiotherapy (SRT) and sequential ICI therapy in PDAC, as well as to validate the efficacy of this regimen as a potential activator of antitumor immunity. Methods Patients aged ≥ 18 years with unresectable non-metastatic PDAC following four FOLFIRINOX induction cycles were included. Treatment comprised SRT (4 × 8 Gy) and sequential nivolumab administration until disease progression or unacceptable toxicity. The primary endpoints were safety and toxicity assessment. Secondary endpoints included progression-free survival (PFS), overall survival (OS), biomarker evaluation, and quality of life (QoL) analysis. Results Twenty-two patients were screened, with 15 enrolled. Eleven (median) nivolumab cycles were administered. SRT demonstrated low and clinically nonsignificant toxicity, whereas nivolumab toxicity aligned with prior safety profiles, without grade 4–5 events observed. Three patients discontinued therapy owing to toxicity. Median PFS and OS were 8.1 and 13.0 months, respectively, with 12-month PFS and OS rates of 0% and 66.7%, respectively, and a 24-month OS rate of 8.9%. Biomarker levels correlated with clinical or radiological disease control. Patient-reported QoL remained acceptable, deteriorating with disease progression. Conclusion SRT and nivolumab therapy exhibited manageable toxicity profiles consistent with previous findings; however, long-term treatment responses were not achieved with this regimen in locally advanced PDAC. Another strategy to trigger antitumor immunity in PDAC needs to be sought. Trial Registration EudraCT: 2017–003404-52; ClinicalTrials.gov: NCT04098432.